If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3n + 6 + 5n = 7n + -8n + -9 Reorder the terms: 6 + -3n + 5n = 7n + -8n + -9 Combine like terms: -3n + 5n = 2n 6 + 2n = 7n + -8n + -9 Reorder the terms: 6 + 2n = -9 + 7n + -8n Combine like terms: 7n + -8n = -1n 6 + 2n = -9 + -1n Solving 6 + 2n = -9 + -1n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add 'n' to each side of the equation. 6 + 2n + n = -9 + -1n + n Combine like terms: 2n + n = 3n 6 + 3n = -9 + -1n + n Combine like terms: -1n + n = 0 6 + 3n = -9 + 0 6 + 3n = -9 Add '-6' to each side of the equation. 6 + -6 + 3n = -9 + -6 Combine like terms: 6 + -6 = 0 0 + 3n = -9 + -6 3n = -9 + -6 Combine like terms: -9 + -6 = -15 3n = -15 Divide each side by '3'. n = -5 Simplifying n = -5
| 4x^2-9x+23=7x+8 | | 7x-2y=-14 | | x^6+5=26 | | 6x+11=75-2 | | x^4=-10 | | x^4=20 | | 9(4x+1)=3x-6x | | 1/4-x=3/8 | | -2x-5=21 | | 59-2x=7x+20 | | -x+3=4x+7 | | 9(4x-1)=3x-6x | | -3+10=2x+8+1 | | 5x-2=6(x-6) | | 7x-6w= | | 9-8x=29-15x | | 15x-4=12x-7 | | 16a+19b+6c+3c-2b-3a= | | x+x+7.7=720.3 | | 0.6=-0.4x | | 5(2x-1)+3(4-9x)= | | 10a*4=71-9 | | 18p+15q+p-3q-4p= | | 29x-3=41-2x | | 5(4x+7)=-36+51 | | 57x+8=1.26 | | 6x-5-3x=4x-42 | | 1x-2=-6 | | 38-2x=-6x+6 | | 5(x-4)=4(x+5) | | 5+2(p-3)=4(p+2)-8 | | 7x-7=7(x-2)+5 |